Computational Study Potency of Eugenol and Safrole Derivatives as Active Sunscreen Material - Yusthinus Thobias Male; I Wayan Sutapa; Mirella Fonda Maahury; Muhamad Jamal; Dominggus Male (Molekul, 2022)
Computational studies have been carried out on eugenol and safrole derivatives as active sunscreen materials. The calculations were using Density Functional Theory (DFT) with the B3LYP functional and basis set 6-31G (d). The calculated eugenol derivative i.e. 3,4-dimethoxy isobutyl cinnamate; 3,4-dimethoxy isoamyl cinnamate; 3,4-dimethoxy isohexyl cinnamate; 3,4 dimethoxy isoheptyl cinnamate; 3,4-dimethoxy isoctyl cinnamate. The calculated safrole i.e. 3,4-methylenedioxy isobutyl cinnamate; 3,4-methylenedioxy isoamyl cinnamate; 3,4-methylenedioxy isohexyl cinnamate; 3,4-methylenedioxy isoheptyl cinnamate; and 3,4-methylenedioxy isooctyl cinnamate. The main parameter in determining the potential of sunscreen compounds is energy gap. The results of computational calculations show that the 3,4-methylenedioxy isohexyl cinnamate has the smallest energy gap (HOMO-LUMO) of 0.15021 eV. This shows that 3,4-methylenedioxy isohexyl cinnamate has a better potential as an active sunscreen material. In addition, the elongation of the alkyl chain does not significantly affect the HOMO-LUMO energy difference